Evaluating the outcomes of collaborative wildlife governance: The role of social-ecological system context and collaboration dynamics. (December 2020) - Dressel, S.; Ericsson, G.; Johansson, M.; Kalén, C.; Pfeffer, S.E.; Sandström, C.
Highlights: Environmental governance evaluations should study context, processes and outcomes. We combined survey responses with ecological monitoring data within a path model. The social-ecological context directly affected collaboration dynamics and outcomes. Actors knowledge and time investment had positive effects on ecological outcomes. Adapting institutions to the social-ecological context might enhance effectiveness. Abstract: The acknowledgement of uncertainty and complexity in social-ecological systems has increased the implementation of collaborative governance regimes for environmental issues. The performance of these new regimes to deliver favourable social and ecological outcomes must therefore be evaluated. We focus on the case of Swedish wildlife governance, which has a tradition of using collaborative elements. In relation to moose ( Alces alces ), these collaborative aspects were recently formalized in an amended policy. We aim to assess some aspects of this new regime's performance with respect to intermediate ecological outcomes (i.e. quota fulfilment). We use path analysis to test the causal effects of system context and collaboration dynamics on governance outcomes. Collaboration dynamics were assessed using a web-based survey sent to all stakeholders in Moose Management Groups (response rate = 82 %). Our originally specified model yielded a good fit (SRMR of .030 and robust TLI of .996) and explained 20 % of the variation in outcomes. Context variables revealed significant direct effects on collaboration dynamics and outcomes. Larger Moose Management Areas and fluctuations in forage availability required more time investment from actors, while high land use diversity and density of other ungulate species negatively affected moose quota fulfilment. Moose Management Groups that invested more time and perceived to have a good knowledge base achieved better quota fulfilment. Collaboration dynamics thus had a positive direct effect on outcomes. From a policy perspective, our results raise questions regarding institutional fit because context factors had significant negative effects on collaboration dynamics and the outcomes of the collaborative process.